2011
DOI: 10.1155/2011/692102
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Testing for Chronic Pelvic Pain: Discriminating Visceral from Somatic Pain

Abstract: Objectives. This study was done to evaluate three bedside tests in discriminating visceral pain from somatic pain among women with chronic pelvic pain. Study Design. The study was an exploratory cross-sectional evaluation of 81 women with chronic pelvic pain of 6 or more months' duration. Tests included abdominal cutaneous allodynia (aCA), perineal cutaneous allodynia (pCA), abdominal and perineal myofascial trigger points (aMFTP) and (pMFTP), and reduced pain thresholds (RPTs). Results. Eighty-one women were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…Jarrell et al have shown that abdominal cutaneous allodynia, reduced pain thresholds, and abdominal wall trigger points are associated with pelvic pain of visceral origin. 20 We do not have data on cutaneous allodynia or pain thresholds, but our observed association between pelvic floor tenderness and abdominal wall pain (trigger points) confirms a role of visceral pain in our population. Our observation of an association between pelvic floor tenderness and bladder base tenderness also confirms the bladder as another source of visceral pain in this population.…”
Section: Discussionsupporting
confidence: 45%
“…Jarrell et al have shown that abdominal cutaneous allodynia, reduced pain thresholds, and abdominal wall trigger points are associated with pelvic pain of visceral origin. 20 We do not have data on cutaneous allodynia or pain thresholds, but our observed association between pelvic floor tenderness and abdominal wall pain (trigger points) confirms a role of visceral pain in our population. Our observation of an association between pelvic floor tenderness and bladder base tenderness also confirms the bladder as another source of visceral pain in this population.…”
Section: Discussionsupporting
confidence: 45%
“…To study this, we infected donor NOD mice with CP-1, isolated serum and T cells (Pan T) and transferred them into naïve NOD mice (five per group) that were unexposed to CP-1. Recipient mice were tested at baseline and over time for the development of suprapubic tactile allodynia, a consequence of referred hyperalgesia and a characteristic of visceral pain [10][12]. While tactile allodynia was not changed in the group administered immune serum or naïve serum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Behavior testing was based on the concept of cutaneous hyperalgesia resulting from referred visceral pain [10][12]. An irritable focus in visceral tissues reduces cutaneous pain thresholds allowing for an exaggerated response to normally non-painful stimuli (allodynia).…”
Section: Methodsmentioning
confidence: 99%
“…Behavior testing was based on the concept of cutaneous hyperalgesia resulting from referred visceral pain [8][9][10] . An irritable focus in visceral tissues reduces cutaneous pain thresholds allowing for an exaggerated response to normally non-painful stimuli (allodynia).…”
Section: Introductionmentioning
confidence: 99%